2022
DOI: 10.1101/2022.08.31.505981
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

From sequence to function through structure: deep learning for protein design

Abstract: The process of designing biomolecules, in particular proteins, is witnessing a rapid change in available tooling and approaches, moving from design through physicochemical force fields, to producing plausible, complex sequences fast via end-to-end differentiable statistical models. To achieve conditional and controllable protein design, researchers at the interface of artificial intelligence and biology leverage advances in natural language processing (NLP) and computer vision techniques, coupled with advances… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 119 publications
0
3
0
Order By: Relevance
“…They have also been employed to understand the language of nucleic acids (DNA/RNA) and proteins. Protein language models (pLMs), using amino acid alphabets, are the most heavily investigated biological LLMs Rives et al (2021); Elnaggar et al (2022), with demonstrated success in downstream tasks such as protein function prediction Unsal et al (2022) and engineering Ferruz et al (2022). Nucleotide LLMs, using DNA/RNA alphabets, are still understudied Avsec et al (2021).…”
Section: Current State Of the Artmentioning
confidence: 99%
“…They have also been employed to understand the language of nucleic acids (DNA/RNA) and proteins. Protein language models (pLMs), using amino acid alphabets, are the most heavily investigated biological LLMs Rives et al (2021); Elnaggar et al (2022), with demonstrated success in downstream tasks such as protein function prediction Unsal et al (2022) and engineering Ferruz et al (2022). Nucleotide LLMs, using DNA/RNA alphabets, are still understudied Avsec et al (2021).…”
Section: Current State Of the Artmentioning
confidence: 99%
“…They have also been employed to understand the language of nucleic acids (DNA/RNA) and proteins. Protein language models (PLMs), using amino acid alphabets, are the most heavily investigated biological LLMs (Elnaggar et al, 2022, Rives et al, 2021, with demonstrated success in many downstream tasks (e.g., protein function prediction (Unsal et al, 2022)) and engineering (Ferruz et al, 2022). Nucleotide LLMs, using DNA/RNA alphabets, are still understudied (Avsec et al, 2021).…”
Section: Large Language Models (Llms)mentioning
confidence: 99%
“…The rapid development of deep learning has opened up a new method to acquire novel P450s with desired characteristics. Even though impressive achievements have been witnessed in protein structure prediction 17, 18 , the desired functional design still is a big challenge 19, 20 . Recent developments in protein design leveraged by deep learning methods encompass a broad spectrum.…”
Section: Introductionmentioning
confidence: 99%